2019
DOI: 10.1212/nxg.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function mutations in Lysyl-tRNA synthetase cause various leukoencephalopathy phenotypes

Abstract: ObjectiveTo expand the clinical spectrum of lysyl-tRNA synthetase (KARS) gene–related diseases, which so far includes Charcot-Marie-Tooth disease, congenital visual impairment and microcephaly, and nonsyndromic hearing impairment.MethodsWhole-exome sequencing was performed on index patients from 4 unrelated families with leukoencephalopathy. Candidate pathogenic variants and their cosegregation were confirmed by Sanger sequencing. Effects of mutations on KARS protein function were examined by aminoacylation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Thus, we diagnosed this patient's condition as KARS-related progressive leukodystrophy with cerebral calcification, involvement of corticospinal tracts, congenital deafness, and evidence of mitochondrial dysfunction. [1][2][3][4] As both MRS and mitochondrial oxygen consumption rate in fibroblasts showed evidence of mitochondrial dysfunction in our patient, we started him on vitamin supplementation (B1, C, E, biotin, carnitine, and CoQ 10 ) at the age of 5 years and 8 months. In addition, to correct his abnormal mitochondrial function, we started him on a KD with a ketone-to-nonketone ratio of 3:1 at 5 years and 10 months.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, we diagnosed this patient's condition as KARS-related progressive leukodystrophy with cerebral calcification, involvement of corticospinal tracts, congenital deafness, and evidence of mitochondrial dysfunction. [1][2][3][4] As both MRS and mitochondrial oxygen consumption rate in fibroblasts showed evidence of mitochondrial dysfunction in our patient, we started him on vitamin supplementation (B1, C, E, biotin, carnitine, and CoQ 10 ) at the age of 5 years and 8 months. In addition, to correct his abnormal mitochondrial function, we started him on a KD with a ketone-to-nonketone ratio of 3:1 at 5 years and 10 months.…”
Section: Introductionmentioning
confidence: 84%
“…11,13 These findings are the case in our patient and previously reported patients with KARS mutations. [1][2][3][4] From these facts, some researchers assumed that dysfunction of mitochondrial ARS is more likely to be contributing to the pathogenesis of these disorders. Whereas, one study revealed that a reduced activity of cytoplasmic isoform of lysyl-tRNA synthetase and a slightly increased activity of mitochondrial isoform were expressed in fibroblasts of patients with KARS mutations and a reduced activity of the complexes I and IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variable clinical presentation of the disease has been associated with the KARS gene mutations; all those disorders, have been linked to an autosomal recessive inheritance pattern mechanism [12,13]. Among the most affected organs, are those with high energy demand such as the brain, heart, skeletal muscle and kidneys, probably secondary to the mitochondrial disfunction with a secondary impaired oxidative phosphorylation [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an etiology of the patient's condition, a WES was performed where two variants in the KARS gene were identified; the variant c.1514G > A (p.Arg505His) classified as pathogenic (rs778748895) previously reported in the Literature (4,11,12). The variant c.371G > A (p.Ala526Val), which has been classified as probably pathogenic, has not been previously reported in the literature.…”
Section: Genetic Studiesmentioning
confidence: 99%